DEVELOPMENT OF LEARNING PROGRESSION MODELING-BASED TEACHING (LP-MBT) FOR STUDENTS WITH LEARNING DIFFICULTIES IN INCLUSIVE CLASSROOMS - Teguh Prasetyo; Asep Supena; Rasmitadila Rasmitadila; Widyasari Widyasari (Pedagogi, 2021)
Understanding student characteristics and the process of designing learning according to students with special needs are the main weaknesses of lecturers in inclusive classes. Students often complain that lecturers' learning is still monotonous, lack of variation in learning strategies, and the absence of learning media so that students experience difficulties in the process of visualizing the content of teaching materials in class. The research objective was to develop Learning Progression during Modeling-Based Teaching (LP-MBT) to help students with learning difficulties in higher education. The research method used in research and development follows Thiagarajan's (1974) 4-D model but is only applied to 3-D, namely the define, design, and developing stages. This preliminary research study involved three student respondents with special needs and twelve regular students from Elementary School Teacher Education students at Djuanda University. The research was conducted during the odd semester of the 2020/2021 academic year. The process of collecting research data was carried out using questionnaires and semi-structured interviews through online or online applications. The research results are as follows; (1) the define stage, the researcher analyzes the problems of students with special needs in the learning process in the classroom; (2) in the design stage, researchers designed Learning Progression during Modeling-Based Teaching (LP-MBT) in inclusive classroom learning based on theoretical studies and the needs of students with learning difficulties; and (3) the developing stage, the researcher validates the experts and conducts limited trials for 15 students online through the zoom application. Suggestions from this study, the Learning Progression during Modeling-Based Teaching (LP-MBT) design can be used for students with special needs, especially learning difficulties because it can activate the learning content visualization process for students and provide opportunities to express more equitable opinions.